The ant's picnic - Khan , Saniyasnain (goodwordkidz : India, 2003)
In this engaging tale, a group of ants embarks on a picnic adventure. As they venture out, they encounter various foods and challenges, learning about teamwork and the importance of sharing. The story is designed to support vocabulary development, particularly in food-related terms, and introduces young readers to concepts like plurals, sequencing, and pronouns. Additionally, the book includes activity suggestions to further enhance learning